2014
DOI: 10.1007/s10118-015-1581-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting exopolysaccharides produced by selected bacteria associated with marine organisms for biotechnological applications

Abstract: In this study, bacteria associated with marine organisms were screened for the production of exopolysaccharides (EPSs) on MY media containing sea salts (2.5%10%). Three selected isolates were identified as Alteromonas sp. PRIM-21, Nitratireductor sp. PRIM-24 and Enterobacter sp. PRIM-26 using 16S rRNA gene sequencing. Optimization of the growth and EPS production kinetics in relation to incubation time were assessed. The purified EPS yield was 590, 650 and 540 mg·L 1 culture media respectively in Alteromonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Marine halophilic bacterial EPS have been concerned due to their novel characteristics and good antioxidant activity. Priyanka et al [61] isolated a sulfated EPS mainly consisting of glucose and having a molecular weight of 269 kDa from the marine halophilic strain Labrenzia sp. PRIM-30.…”
Section: Bacterial Polysaccharidesmentioning
confidence: 99%
“…Marine halophilic bacterial EPS have been concerned due to their novel characteristics and good antioxidant activity. Priyanka et al [61] isolated a sulfated EPS mainly consisting of glucose and having a molecular weight of 269 kDa from the marine halophilic strain Labrenzia sp. PRIM-30.…”
Section: Bacterial Polysaccharidesmentioning
confidence: 99%
“…In consistent with our findings, several studies have shown the non-toxic nature of EPSs on different cell line models. 46,49,50 Regarding the no cytotoxicity effect of the EPSs on normal cell line of MDCK, it seems they have biocompatibility features. The biocompatibility is one of the desirable properties of the natural polymers for use in the formulation of food products, medicines and cosmetics.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…The same organism was used by Raguénès et al [183], who described for the first time a new microorganism, affiliated to the Vibrio genus, named Vibrio diabolicus, as being able to produce an innovative exopolysaccharide. Priyanka et al [184] collected several marine organisms, and isolated three EPS-producing strains, i.e., Alteromonas sp. PRIM-21 from a marine seaweed, Nitratireductor sp.…”
Section: Extracellular Polymeric Substances (Epss)mentioning
confidence: 99%